How ISIS fights: military tactics in Iraq, Syria, Libya and Egypt - Ashour, Omar (Edinburgh University Press, 2021)
How did ISIS - a widely hated, massively outnumbered and ludicrously outgunned organisation - manage to occupy over 120 cities, towns and villages from the Southern Philippines to Western Libya? Seeking to understand ISIS's combat effectiveness, Omar Ashour analyses the military and tactical innovations of ISIS and their predecessors in Iraq, Syria, Libya and Egypt. He shows how their capacity to mix conventional military tactics with innovative guerrilla warfare and urban terrorism strategies allowed ISIS to expand and endure beyond expectations.